MiR-223-3p in Cardiovascular Diseases: A Biomarker and Potential Therapeutic Target - Zhang, Meng-Wan; Shen, Yun-Jie; Shi, Jing; Yu, Jian-Guang (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases, involving vasculopathy, cardiac dysfunction, or circulatory disturbance, have become the major cause of death globally and brought heavy social burdens. The complexity and diversity of the pathogenic factors add difficulties to diagnosis and treatment, as well as lead to poor prognosis of these diseases. MicroRNAs are short non-coding RNAs to modulate gene expression through directly binding to the 3’-untranslated regions of mRNAs of target genes and thereby to downregulate the protein levels post-transcriptionally. The multiple regulatory effects of microRNAs have been investigated extensively in cardiovascular diseases. MiR-223-3p, expressed in multiple cells such as macrophages, platelets, hepatocytes, and cardiomyocytes to modulate their cellular activities through targeting a variety of genes, is involved in the pathological progression of many cardiovascular diseases. It participates in regulation of several crucial signaling pathways such as phosphatidylinositol 3-kinase/protein kinase B, insulin-like growth factor 1, nuclear factor kappa B, mitogen-activated protein kinase, NOD-like receptor family pyrin domain containing 3 inflammasome, and ribosomal protein S6 kinase B1/hypoxia inducible factor 1 α pathways to affect cell proliferation, migration, apoptosis, hypertrophy, and polarization, as well as electrophysiology, resulting in dysfunction of cardiovascular system. Here, in this review, we will discuss the role of miR-223-3p in cardiovascular diseases, involving its verified targets, influenced signaling pathways, and regulation of cell function. In addition, the potential of miR-223-3p as therapeutic target and biomarker for diagnosis and prediction of cardiovascular diseases will be further discussed, providing clues for clinicians. The future application of miR-223-3p in clinical situations may depend on further determination of its specific role in diverse cardiovascular diseases and the accurate delivery to target organs or cells.